Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan Pada Perusahaan Consumer Goods - Gisela Nindita Taslim, Hendang Tanusdjaja (Jurnal Paradigma Akuntansi, 2019)
The purpose of this study is to find the effects of financial leverage, asset returns, firm size and sales growth on firm’s value in consumer goods companies listed on the Indonesia Stock Exchange for the period 2015-2017. This research uses 39 consumer goods companies that have been selected using purposive sampling method from a total of 46 companies during three years and produced 117 company data samples. The data used are secondary data that contains company financial statements and company performance reports. Processing carried out in this study uses Eviews software. The results of this study indicate that financial leverage and asset returns have a positive and significant effect on firm value, but for company size and sales growth do not have a significant effect on firm value.